"It saves lives": Peer support and resilience in transgender and gender diverse communities - Hannah Kia; K Kenney; Kinnon Ross MacKinnon; Alex Abramovich; Travis Salway; Olivier Ferlatte; Rod Knight; Grant Charles; Sheila K. Marshall (Elsevier, 2023)
Transgender (trans) and gender diverse (TGD) populations continue to experience significant inequities in social and health outcomes, often in connection with the systemic exposure of these groups to violence, stigma, and discrimination. Despite the promising role of peer support in mitigating adverse impacts of marginalization, this phenomenon remains under-examined. In this study, which is informed methodologically by an abductive approach to grounded theory and anchored theoretically in scholarship on critical resilience and intersectionality, we draw on individual semi-structured interviews with 35 TGD individuals located in two major cities in Canada (Toronto and Vancouver) to examine experiences of peer support. We also consider the role of peer support in building resilience among participants. Our findings are organized into four interrelated themes that both represent the constituent parts of peer support, and that explicate the connections between peer support and resilience. These include: (1) becoming visible to connect with similar others, (2) sharing embodiment, experience, and space, (3) constructing possibilities of being and collectivizing, and (4) surviving and thriving (at a cost). We leverage our findings to consider implications for research, policy, and practice, one of which includes the need for ongoing inquiry to substantiate the critical role of peer support in promoting health across diverse TGD communities.